Disharmoni Sosial Masyarakat Kampung Kota di Era Demokratisasi (Konflik dan Disharmoni Sosial di Yogyakarta Pada Pilpres tahun 2019) - Arifin, Muhammad (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
Democracy that has lasted so far is not only understood as an effort to build a better government system but is also intended as an effort to create citizen participation in building a good political and governance system. But in reality, it does not produce a sense of security, peace, order and social order. This paper is intended to look at the phenomenon of democracy, especially election practices, not only from a political and power perspective, but also to see how elections actually create social disharmony in the Yogyakarta city community. This paper is based on one argument, namely: that democracy is intended to build a more open, just, peaceful and prosperous society that does not work properly because the understanding and practices of democracy that have been practiced so far have actually led to increased resistance and social disharmony. This paper uses a qualitative analytical method with data sourced from direct observation and from local newspapers. From this research it was found that (1) social conflict in villages, especially in Yogyakarta is getting higher and social resistance is increasing; (2) Community grouping, and segregation tend to be based on religious and political affiliations; and village gangs (3) Villages that used to be administratively separated, were instead claimed as the village of certain groups which referred to certain religious-based groups or parties. From this paper it can be concluded that the conflicts that occurred in the city of Yogyakarta during the 2019 presidential election were more caused by village-based sentiments and solidarity of certain parties and groups rather than conflicts between elites.